2014
DOI: 10.3727/096368913x667024
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Integration of Developing and Progenitor-Derived Retinal Ganglion Cells following Transplantation

Abstract: There is considerable interest in transplanting stem cells or progenitors into the injured nervous system and enhancing their differentiation into mature, integrated, functional neurons. Little is known, however, about what intrinsic or extrinsic signals control the integration of differentiated neurons, either during development or in the adult. Here we ask whether purified, postmitotic, differentiated retinal ganglion cells (RGCs) directly isolated from rat retina or derived from in vitro-differentiated reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 37 publications
3
72
1
1
Order By: Relevance
“…The challenge now is that these seeded neurons must be integrated into the surviving circuitry to re-establish lost connections. A recent study demonstrated that embryonic and neonatal RGCs seeded into the adult retina integrate into the ganglion cell layer and project neurites in the IPL, where synapses may be formed [95]. How well transplanted neurons reinstate their detailed circuitry and functions remains to be elucidated.…”
Section: Challenges To Circuit Repair After Remodeling In Diseasementioning
confidence: 99%
“…The challenge now is that these seeded neurons must be integrated into the surviving circuitry to re-establish lost connections. A recent study demonstrated that embryonic and neonatal RGCs seeded into the adult retina integrate into the ganglion cell layer and project neurites in the IPL, where synapses may be formed [95]. How well transplanted neurons reinstate their detailed circuitry and functions remains to be elucidated.…”
Section: Challenges To Circuit Repair After Remodeling In Diseasementioning
confidence: 99%
“…[12] However, RGC transplantation is inherently more difficult than photoreceptor transplantation, as it requires the transplanted cells to integrate dendritically with their amacrine or bipolar cell presynaptic partners in the inner plexiform layer, extend their axons radially through the retina to the optic nerve, grow down the optic nerve and find their appropriate targets in the brain. Previously, we investigated the use of both PLL-PEG hydrogels [26] and PLA electrospun scaffolds [27] to study RGC survival and neurite growth and as a potential cell delivery vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, transplanted RGCs have been observed to project dendritic processes into the inner plexiform layer,[12] and stem cells transplanted directly onto the optic nerve head are able to project a process through the optic nerve head. [13] However, transplanted cells located away from the optic nerve head were unable to extend their axons radially as occurs with endogenous RGCs in the normal retina.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical data have shown that primary RGCs and RP cellderived RGCs differentiated in vitro are able to survive transplantation intravitreally, migrate to the retina and in some cases, integrate into the ganglion cell layer with neurites extending into the nerve fiber layer and inner plexiform layer [81]. Aoki et al showed that, once implanted, ESC-derived eye-like structures contained cells that could differentiate into RGC-like cells in the host ganglion cell layer [82].…”
Section: The 3d Optic Nerve Modelmentioning
confidence: 98%